Health Technology Assessment (HTA) of virtual autopsy through PMCT with particular focus on Italy. (September 2022) - Filograna, Laura; Manenti, Guglielmo; Grassi, Simone; Zedda, Massimo; Ryan, Colleen P.; Floris, Roberto; Oliva, Antonio
Highlights: PMCT is used as a routine investigative modality in many forensic institutions. HTA is used for assessing medical innovations and healthcare systems. PMCT is a valuable method in forensic investigations, also considering added costs. The greatest benefits are expected after the implementation of dedicated CT scans. Abstract: Objectives: Over the last decades interest has grown in the use of virtual autopsy through PMCT as an adjunct or alternative to the invasive autopsy. Health technology assessment (HTA) is currently one of the major challenges in assessing medical innovations and healthcare systems. This paper is focused on HTA applied to unenhanced PMCT with the aim to evaluate the impact of this technology in forensic investigations with particular focus on Italy. Materials and methods: In this paper EUnetHTA Core Model individual domains were applied to unenhanced PMCT virtual autopsy. Results: This is the first pilot HTA report using the HTA Core Model regarding virtual autopsy. Virtual autopsy provides many advantages in comparison to traditional autopsy such as the reduction of infection risk, guidance for subsequent autopsy, and moreover allows archiving of data that can be viewed and analyzed in the future by various experts. PMCT can add important information to traditional autopsy and in selected cases, has been proposed as a replacement for classical autopsy, the current gold standard. Conclusions: Unenhanced PMCT is a valuable technique in terms of advantages provided, also considering added costs. Based on the results of our analysis, we recommend a larger introduction of this technology in forensic investigations. The greatest benefits are expected after the implementation of dedicated CT scans for post-mortem examinations, that would simplify workflow and the management of cadavers. Thus, we recommend a significant inclusion of PMCT in forensic investigations. Graphical abstract: Image, graphical abstract